Description of a new water mite of the genus Arrenurus (Acari, Hydrachnidia: Arrenuridae) from Chukotka - Tuzovskij, Petr V. (Zootaxa, 2020)
This paper describes a new water mite species of the family Arrenuridae. Specimens were collected by the author in standing waters of the Asian part of Russia with a common hand net with 250 μm. Most specimens were not dissected, thus preserving natural shape of the body. For several larvae, males and females the gnathosoma was mounted in a position that allowed examnation of the pedipalps in lateral view. To obtain larvae, water mites were maintained in laboratory (room temperature, natural day-night conditions). Eggs and larvae obtained from single female in glass with diameters 10 mm, and a height 15 mm.